Odpowiedź:
a) 3x + 7 = 5 /-7
3x = -2 /:3
x = [tex]-\frac{2}{3}[/tex]
b) -2x - 3 = -4x + 8 /+3
-2x = -4x +11 /+4x
2x = 11 /:2
x = 5,5
c) -3x + 3 = 7 /-3
-3x = 4 /:(-3)
x= -1[tex]\frac{1}{3}[/tex]
d) -2x - 3 = -x /+2x
x = -3
e) -5x = 7 - 3x /+3x
-2x = 6 /:(-2)
x = -3
f) -5 + 2x = 7 - 3x /+3x
-5 + 5x = 7 /+5
5x = 12 /:5
x = 2[tex]\frac{2}{5}[/tex]
g) 8 - 3x = 7 - 2x /+3x
8 = 7 + x /-7
x = 1
h) 5x - 3 = 5 /+3
5x = 8 /:5
x = 1[tex]\frac{3}{5}[/tex]
i) 7+2x = 1 /-7
2x = -6 /:2
x = -3
Szczegółowe wyjaśnienie: